A Cre‐inducible fluorescent reporter for observing apical membrane dynamics. Issue 3 (11th April 2015) - Pan, Xinchao; Schnell, Ulrike; Karner, Courtney M.; Small, Erin V.; Carroll, Thomas J.
Summary: The ability to image living tissues with fluorescent proteins has revolutionized the fields of cell and developmental biology. Fusions between fluorescent proteins and various polypeptides are allowing scientists to image tissues with sub‐cellular resolution. Here, we describe the generation and activity of a genetically engineered mouse line expressing a fusion between the green fluorescent protein (GFP) and the apically localized protein Crumbs3 (Crb3). This reporter drives Cre‐inducible expression of Crb3–GFP under control of the EF1a regulatory domains. The fusion protein is broadly expressed in embryonic and adult tissues and shows apical restriction in the majority of epithelial cell types. It displays a variably penetrant gain of function activity in the neural tube. However, in several cell types, over‐expression of Crb3 does not appear to have any effect on normal development or maintenance. Detailed analysis of kidneys expressing this reporter indicates normal morphology and function highlighting the utility for live imaging. Thus, the EF1a Crb3–GFP mouse line will be of broad use for studying membrane and/or tissue dynamics in living tissues. genesis 53:285–293, 2015. © 2015 Wiley Periodicals, Inc.